Climate change education: the problem with walking away from disciplines - Eilam, Efrat (Studies in science education, 2022)
Globally climate change (CC) is scarcely addressed in school curricula, and school graduates are mostly uneducated about climate change. The purpose of this paper is to make a case for conceptualising CC as a discipline, and to further argue why CC should be included in school curricula as a disciplinary-subject. An initial examination of CC in curricula globally reveals that the main approach for including CC in the curriculum is the cross-curriculum approach. The problems associated with this approach are discussed in regard to the challenges posed to the integrity of the CC body of knowledge, and to the teaching and learning. The paper continues to build a case for conceptualising CC as a discipline in its own right. It explains the notions of: disciplines, subjects, and disciplinary-subjects. Further, it describes the disciplinary characteristics of CC, and the benefits of including CC in the curriculum as a disciplinary-subject. However, curricular resistance issues are identified and discussed. These resistances are addressed by considering evidence derived from curriculum theory, cognitive psychology and philosophy of science for supporting the inclusion of a CC disciplinary-subject. Finally, the challenges in establishing a CC disciplinary-subject are discussed. The paper concludes by considering implications for further research.